Village Tourism Development Strategy Through Community Empowerment in Desa Awang Bangkal Timur Martapura, South Kalimantan - Diany, Adista Anjar (DAS Institute, 2025)
This study aims to formulate a village tourism development strategy through community empowerment in Awang Bangkal Timur Village, Martapura, South Kalimantan. The research employed a qualitative descriptive approach with SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify internal and external factors influencing the development of village tourism. The findings reveal that the village’s strengths include beautiful natural potential, unique local culture, and strong community participation. However, weaknesses were identified in terms of limited infrastructure, lack of managerial skills among the community, and insufficient promotion. Opportunities for development are supported by the growing trend of nature- and culture-based tourism as well as government support, while threats include competition from other destinations and the risk of environmental degradation. Based on SWOT analysis, the formulated strategies include strengthening village tourism institutions, enhancing community capacity through training, optimizing digital promotion, implementing ecotourism principles, and fostering collaboration with stakeholders. Community-based village tourism development in Awang Bangkal Timur has the potential to enhance tourism attractiveness while promoting sustainable community welfare.